STRUKTUR ANATOMI BEBERAPA JENIS KAYU HUTAN TANAMAN INDUSTRI - Sri Rulliaty M; Y I Mandang (Pusat Penelitian dan Pengembangan Hasil Hutan, 1988)
Gross and anatomical features of nine Industrial Forest Plantation Timber Species were studied and described for identification purposes. The result shows that each wood species can be distinguished one from the other except those species which belong to the same genera.